CHRISTIAN INDONESIAN’S REACTIONS TO ISLAMIC STATE OF IRAQ AND SYRIA (ISIS) ISSUES ON MASS MEDIA: A CASE STUDY ON THE MASSES OF INDONESIAN BAPTIST CHURCH IN YOGYAKARTA - Suciati,; Nashwan, (International Journal of Psychosocial Rehabilitation, 2020)
Since its emergence as a rebel group, the Islamic State of Iraq and Syria (ISIS) often performed deeds that are inhumane and smeares the good name of Islam. This is clarified by news items in mass media. Every action taken by this movement impacts multiple sides, especially to the Christians as they suffer the most casualties. Therefore, it is important to find out how the Christians feel and react towards the mass media regarding ISIS, which is considered to possess terrorism-related values and is capable of destroying the existing values of tolerance, especially in Indonesia. This issue will be opened with a descriptive research and an interactive qualitative analysis, using a discussion forum on nine chosen informants from the Saman Baptist Church in Sewon, Bantul, Yogyakarta. Each informant will be analyzed through their cognitive, affective, and conative reactions. The results of the research concludes that the informants’ reactions are not only influenced by the mass media, but also from other factors such as profession, Christian religious tendencies, Javanese culture, and motivation.